Pooled prevalence of food away from home (FAFH) and associated non-communicable disease (NCD) markers: a systematic review and meta-analysis - Swapnil Godbharle; Angeline Jeyakumar; Bibek Raj Giri; Hema Kesa (BMC, 2022)
Abstract Background Food away from home (FAFH) is an 'eating behavior' widely practiced across nations, more common in developed nations. Likewise, in developing countries an increase of close to 50% indicates an upsurge in FAFH consumption. While various indices and tools are used to assess diet quality, diversity, or healthy eating, FAFH is less utilized to study dietary behaviors and the associated disease risk. Objective To calculate the pooled estimate of FAFH and identify the associated non-communicable disease (NCD) markers. Design Systematic review and meta-analysis. Methods Independent electronic searches were conducted across 6 databases: Medline, Web of Science, Scopus, Cochrane library, Ingenta, and CAB direct. Observational studies investigating the association between FAFH and NCD markers published between the year 2011 and 2021 were eligible for inclusion. Studies that included overweight or obese participants, pregnant women, or those under institutional care at baseline were excluded. The guidelines for reporting meta-analysis of observational studies in epidemiology were adhered to in the preparation of this systematic review. Results The random effects combined estimate for the overall prevalence of FAFH was 39.96% (95% CI 29.97-53.29). High heterogeneity (τ 2 = 0.63, I 2 = 100%) and high risk of bias were observed among the selected studies. The test for overall effect was observed to be z = 25.11 (p < 0.001). Eleven out of fourteen studies showed a positive association between FAFH and anthropometric changes. Twelve out of seventeen studies showed a positive association between FAFH and cardiovascular disease (CVD) biomarkers. Conclusion Our work confirms FAFH as an evolving dietary behavior in both developing and developed countries, emphasizing the lack of representation from low-income countries. The association of FAFH with obesity and non-communicable disease risk is reinforced by our analyses. These findings should enable policy decisions to meet the rising demand of FAFH with healthier options to prevent the risk of NCD.